2004
DOI: 10.1097/01.mat.0000124954.69612.83
|View full text |Cite
|
Sign up to set email alerts
|

Design and Transient Computational Fluid Dynamics Study of a Continuous Axial Flow Ventricular Assist Device

Abstract: A ventricular assist device (VAD), which is a miniaturized axial flow pump from the point of view of mechanism, has been designed and studied in this report. It consists of an inducer, an impeller, and a diffuser. The main design objective of this VAD is to produce an axial pump with a streamlined, idealized, and nonobstructing blood flow path. The magnetic bearings are adapted so that the impeller is completely magnetically levitated. The VAD operates under transient conditions because of the spinning movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…In comparison, the Thoratec BVAD consists of two pneumatic pump systems with mechanical valves. Analysis of blood flow and shear stress obtained by computer simulations [24] and magnetic resonance (MR) analysis [25] could contribute to design less aggressive biventricular support systems.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the Thoratec BVAD consists of two pneumatic pump systems with mechanical valves. Analysis of blood flow and shear stress obtained by computer simulations [24] and magnetic resonance (MR) analysis [25] could contribute to design less aggressive biventricular support systems.…”
Section: Discussionmentioning
confidence: 99%
“…The implementations of these CFD packages are either based on the finite volume23 method or finite element method. Fluent 36, 37, 38, 39, 40, 41 and CFX 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 11, 57, 58, 59, both available from ANSYS, Inc. (Canonsburg, PA) and STAR-CD from CD-Adapco 60, 61 (Melville, New York) are the CFD software packages used most often for analysis and modelling of blood flow in VADs. In addition, AcuSolve from ACUSIM Software 62 (Mountain View, CA) and Adina from Adina R&D (Watertown, MA) are also used.…”
Section: Computational Techniquesmentioning
confidence: 99%
“…Pumps which have been modelled using the slide mesh approach include Nanyang Technological University’s pump 41 and the Virginia LEV-VAD 50. Song et al 50 performed both steady and transient simulations on the Virginia LEV-VAD and showed that the pressure rise throughout the cardiac cycle varied from 80 to 180 mmHg.…”
Section: Solution Of Flow In a Moving Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients with CF-VADs experienced higher rate of bleeding than those with pulsatile-flow devices although anticoagulation was not different among these two groups of patients. We believe that the increased bleeding risk in patients supported with CF-VADs is associated with the unique high shear stress environment in contemporarily available CF-VADs which has been reported in the literature when compared to pulsatile VADs [10] [1320]. …”
Section: Introductionmentioning
confidence: 99%